Moral Values in the Fable "An-Nahlah wan-Namlah" by Ridwan Syukri: An Actantial and Functional Structure Study - Muhammad Riyadi Nugraha; Muhammad Hasyim; Abdul Muntaqim Al Anshory (Jurnal Sastra Indonesia, 2025)
Children's fable stories are closely related to good values that become a supporting tool for children's growth process. Since narrative in storytelling is critical, this study aims to dissect the potential and functional structure in narratological studies and explore the moral values in the fabled story Al-Nahlah wa An-Namlah by Ridwan Syukri. This story is one of the Arabic children's stories in the Qashah lil Athfal anthology, with most of the stories belonging to the fable genre. The theory used in this research is narratology based on the perspective of A.J. Greimas. The method applied is descriptive qualitative. The data sources in this research are divided into two: (1) primary data sources, namely the fabled story An-Nahlah wa An-Namlah by Ridwan Syukri, and (2) secondary data sources, which are taken from various literature reviews to support the analysis process in this study. The data analysis technique follows the perspective of Miles and Huberman, which includes data condensation, data presentation, and conclusion drawing. The results of this study show that the story of Al-Nahlah wa An-Namlah has a perfect actantial structure. In addition, the functional structure fulfills all the required stages according to the functional structure in general. After analyzing both structures, the researcher concluded that there are two central values, namely (1) hard work and (2) care, which are undoubtedly essential to introduce to children to have moral learning since childhood.